Differences in HIV-specific T cell responses between HIV-exposed and -unexposed HIV-seronegative individuals. - Ritchie, A; Campion, S; Kopycinski, J; Moodie, Z; Wang, Z; Pandya, K; Moore, S; Liu, M; Brackenridge, S; Kuldanek, K; Legg, K; Cohen, MS; et al. (2011)
HIV-1-specific T lymphocyte responses in individuals exposed to HIV-1 but who remain persistently seronegative (HESNs) have been reported in some but not all previous studies. This study was designed to resolve unequivocally the question of whether HESNs make HIV-1-specific T cell responses. We performed a blind investigation to measure HIV-1-specific T cell responses in both HIV-1-serodiscordant couples and HIV-1-unexposed seronegative controls (HUSNs). We found low-frequency HIV-1-specific T cells in both HESNs and HUSNs but show that the response rates were higher over time in the former (P = 0.01). Furthermore, the magnitudes of the HIV-1-specific T cell responses were significantly higher among responding HESNs than among HUSNs over time (P = 0.002). In both groups, responses were mediated by CD4 T cells. The responses were mapped to single peptides, which often corresponded to epitopes restricted by multiple HLA-DR types that have previously been detected in HIV-1-infected patients. HIV-1-specific T cell responses in HUSNs and some HESNs likely represent cross-reactivity to self or foreign non-HIV-1 antigens. The significantly greater T cell responses in HESNs, including in two who were homozygous for CCR5Δ32, demonstrates that HIV-1-specific T cell responses can be induced or augmented by exposure to HIV-1 without infection.